Pilot study shows skin-to-skin care with parents improves heart rate variability in preterm infants in the neonatal intensive care unit - Swieter, Erin; Gross, Jessica M.; Stephen, Julia; Watterberg, Kristi; Maxwell, Jessie R. (Frontiers in Pediatrics, 2023)
Background: Skin-to-skin care in the newborn intensive care unit typically lasts for short periods of time and enhances breastfeeding, attachment, and parental self-esteem. Heart rate variability (HRV) increases with gestational age and is a measure of maturation of parasympathetic versus sympathetic autonomic nervous system activity. HRV measurements may be useful in capturing changes in autonomic regulation in response to skin-to-skin care.Objective: To analyze the effects of skin-to-skin care on HRV in preterm infants receiving respiratory support. We hypothesized that skin-to-skin care would result in a more mature pattern of parasympathetic activity.Methods: In this prospective crossover study, infants <30 weeks' gestation and 1-6 weeks postnatal age had HRV recorded for 30 minutes before, during, and after skin-to-skin care sessions. HRV characteristics analyzed included the standard deviation of the normal-to-normal interval (SDNN), the root mean squared of successive differences of normal-to-normal intervals (RMSSD), and the standard deviation of decelerations (SDDec).Results: 10 infants between 25 5/7 -29 6/7 weeks gestational age and 7-41 days postnatal age completed 22 sessions while receiving respiratory support (positive pressure ventilation or nasal cannula oxygen). Two measures of HRV (SDNN and RMSSD) were significantly decreased by the end of the skinto-skin sessions, compared to pre-session values. SDNN decreased from a median of 10.44ms before the session to 6.70ms after being placed back in bed (p<0.05), with RMSSD decreasing from a median of 6.80ms before the session to 4.32ms while being held at the end of 30 minutes (p<0.05).Discussion: Skin-to-skin care with a parent resulted in a more mature autonomic nervous system pattern in preterm infants receiving respiratory support, suggesting physiologic benefit for the infant.No adverse events were seen during any session.